Anty-Aleksander? Wizerunek Demetriusza Poliorketesa w "Żywocie Demetriusza" Plutarcha z Cheronei - Zieliński, Tomasz (Collectanea Philologica, 2021)
The assumption that imitation of Alexander the Great played a key role in the image of Demetrius Poliorcetes has been broadly accepted by many researchers. The main source on this subject is Plutarch’s Life of Demetrius where the author directly compares these two Macedonian kings and depicts Demetrius as a failed imitator of Alexnader. However, the juxtaposition of numerous other parts in that biography with fragments of Life of Alexander demonstrates that Plutarch purpose was creating the image of Demetrius as a sort of anti-Alexander.